2017
DOI: 10.1093/ndt/gfw227
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum albumin level and venous thromboembolic events in a large cohort of patients with nephrotic syndrome

Abstract: Lower serum albumin is a strong independent predictor for VTE events in NS. The risk increases proportionately with declining albumin levels. Clinical trials are needed to determine benefit of prophylactic anticoagulation in NS patients with moderately lower serum albumin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 45 publications
(62 reference statements)
1
54
0
4
Order By: Relevance
“…(8)(9)(10)(11) Recent emerging evidence suggests that low serum albumin concentrations might be linked with an increased risk of VTE; however, the evidence has been conflicting. Whereas some studies have suggested an increased risk of VTE with low serum albumin concentrations, (12)(13)(14) other studies have shown no evidence of any associations. (9,10,15) In addition, majority of these studies were based on cross-sectional or retrospective designs or were conducted in populations with pre-existing diseases such as nephrotic syndrome and cancer.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(8)(9)(10)(11) Recent emerging evidence suggests that low serum albumin concentrations might be linked with an increased risk of VTE; however, the evidence has been conflicting. Whereas some studies have suggested an increased risk of VTE with low serum albumin concentrations, (12)(13)(14) other studies have shown no evidence of any associations. (9,10,15) In addition, majority of these studies were based on cross-sectional or retrospective designs or were conducted in populations with pre-existing diseases such as nephrotic syndrome and cancer.…”
Section: Introductionmentioning
confidence: 98%
“…(9,10,15) In addition, majority of these studies were based on cross-sectional or retrospective designs or were conducted in populations with pre-existing diseases such as nephrotic syndrome and cancer. (12)(13)(14)(15) However, in a recent elegant evaluation based on two population-based cohorts, Folsom and colleagues demonstrated low serum albumin to be a modest marker of increased VTE risk and speculated that the observed association might reflect a hyperinflammatory or a hypercoagulable state. (16) There were however some drawbacks of this study which included (i) inability to evaluate if inflammation might explain the findings, as there were no available measurements of C-reactive protein (CRP) in the study cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…19 Another study on NS patients also reported that serum albumin level of 3-3.99 g/dL would increase the thromboembolic event Correlation between serum albumin level and platelet aggregation value, assessed using ADP concentration of 1 μM in pediatric NS patients risk by 1.5 times, while serum albumin level of 2.5-2.99 g/dL would increase the thromboembolic event risk by 2.2 times, and serum albumin level below 2.5 g/dL would increase the risk by 2.79 times. 11 This study had several limitations. The sample size was considered small for assessing correlations between these variables.…”
Section: Discussionmentioning
confidence: 93%
“…A serum albumin concentration > 4 g/dL was shown to be associated with a low risk of VTE in ambulatory patients with non-hematologic malignancies [32]. Several studies reported that hypoalbuminemia was shown to be an independent risk factor for VTE in the general public [33] and patients with nephrotic syndrome [34]. However, these studies did not reveal whether hypoalbuminemia is not only a VTE risk factor but also a direct cause for VTE, because hypoalbuminemia may reflect inflammation [35] and urinary loss of albumin in kidney disease [34], which were reported the association with VTE [34,35].…”
Section: Discussionmentioning
confidence: 99%